Understanding Study Drug Discontinuation Through EUCLID - Weissler, E. Hope; Mulder, Hillary; Rockhold, Frank W.; Baumgartner, Iris; Norgren, Lars; Blomster, Juuso; Katona, Brian G.; Fowkes, F. Gerry R.; Mahaffey, Kenneth; Bonaca, Marc; Patel, Manesh R.; Jones, W. Schuyler (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Disparities in the care and outcomes of peripheral artery disease (PAD) have been well-established. In part this is due to disparities in enrollment of PAD trial cohorts. However, less attention has been paid to non-random protocol non-adherence after enrollment, which may lead to inaccurate estimates of treatment effects and reduce generalizability of study results. We aimed to ascertain characteristics associated with premature study drug discontinuation in a PAD cohort. Methods: Using data from EUCLID (Examining Use of Ticagrelor in Peripheral Artery Disease), factors associated with study drug discontinuation were assessed using univariable and multivariable Cox proportional hazards models with time to study drug discontinuation as the outcome of interest. Relationships between study drug discontinuation and major adverse cardiovascular events (MACE; cardiovascular death, myocardial infarction, ischemic stroke), major adverse limb events (MALE; acute limb ischemia, major amputation, and lower extremity revascularization), and all-cause hospitalization were assessed. Results: Of 13,842 eligible EUCLID participants, 3,886 (28.1%) prematurely and permanently discontinued study drug over a maximum follow-up of 42 months (annualized rate of 13.2 discontinuations per 100 patient-years). In a multivariable model, premature study drug discontinuation was associated with older age (aHR 1.16, 95%CI 1.14-1.19), eligibility based on prior lower extremity revascularization rather than ABI/TBI criteria (aHR 1.14, 95%CI 1.06-1.23), CLI status (aHR 1.23, 95%CI 1.06-1.42), COPD (aHR 1.36, 95%CI 1.24-1.49), and geographic region. In a multivariable analysis, study drug discontinuation was significantly associated with future MACE (aHR 3.27, 95%CI 2.90-3.67, p<.001), MALE (aHR 1.84, 95%CI 1.63-2.07, p<.001), and all-cause hospitalization (aHR 2.37, 95%CI 2.21-2.54). Conclusions: This analysis of EUCLID demonstrates that premature, permanent discontinuation of study drug is relatively common in more than a quarter of PAD patients, is unevenly distributed based on geography and other baseline characteristics, and is associated with worse outcomes in a clinical trial context. Study teams leading future PAD trials may want to address the possibility of study drug discontinuation prospectively, as a proactive approach may help investigators to maintain study cohort diversity and representativeness without sacrificing power and precision.